Color Quality Versus Energy Efficiency: A Dual Perspective on LED Retrofits in Healthcare Examination Rooms - Irena Fryc; Maciej Listowski; Christophe Martinsons (Applied Sciences)
Selecting LED retrofits for examination rooms in healthcare buildings involves setting the right balance between lighting quality and energy efficiency. In the case of LEDs incorporated in luminaires used in medical examination rooms, it is essential to consider not only the correlated color temperature (CCT) and color rendering index (CRI Ra) in compliance with the lighting standards, but also the cyanosis observation index (COI) that meets the more demanding regulations of certain countries. In this work, the Color Preference Criteria (CPC) method is used to select LED retrofits for this application. The LEDs classified as P1 according to the CPC method were found to meet the required COI level.